ANALYSIS OF CONSTRUCTIVE CHARACTERISTICS OF THE SUPPLY ZONE SUPPLY CYLINDER OF SPINNING MACHINES - Murodov Orif Jumayevich; Panjiyev Orifjon Erkinovich; Qo‘shboyev Dilmurod Shavkatjon o‘g‘li (Web of Journals Publishing, 2025)
In the article, the main stages of fiber impact in the discretizer drum: supply, discretization, transportation, separation, and then cross-connected transportation with air are carried out.
Keywords: spinning machine, discretization, discretization drum, fiber, tape, feeding cylinder, rubber sleeve, speed, grip angle, hardness, deformation, radius.